BUDAYA PENGGUNAAN SIRIH PADA TRADISI MELAYU RIAU - Amanan Amanan (Ensiklopedia of Journal, 2022)
In ancient times the use of betel for Malays was very important, starting from opening/starting a negotiation event or to summoning (inviting) someone to attend an event such as a marriage ceremony, circumcision ceremony (Rasul Circumcision), the birth of a baby, and a few days after his birth. the parents of the baby use the services of a village midwife to bathe the baby in the river by using a potion in which there is betel. Betel is also used to show a sense of courtesy/hospitality when visiting someone's house such as a friend/neighbor. The Malays serve betel nut to guests visiting their homes, to honor the spirits of their ancestors by making/giving offerings. In the offering, betel leaf is one of the ingredients and to increase energy or readiness to have sex. Malay people also use betel nut and even people use betel nut as a regalia (symbol of royal greatness), but the use of betel nut from year to year is decreasing (fading) or in other words starting to rarely use it.